Users' Acceptance of Artificial Intelligence-Based Chatbots: An Empirical Study - Goli, Mahendar; Sahu, Anoop Kumar; Bag, Surajit; Dhamija, Pavitra (International journal of technology and human interaction, 2023)
This research examines the effects of factors such as perceived ease of use, perceived usefulness, perceived enjoyment, innovativeness, perceived information quality, and perceived customisation on behavioural intention to use Chatbots. The research model designed is empirically validated using structural equation modelling with the aid of AMOS software. A five-point Likert scale-based structured questionnaire was used to collect data from 378 Chatbot users in an online method. The results indicated that the perceived ease of use, perceived usefulness, innovativeness, perceived information quality, and perceived customisation have positive effects on intention to use Chatbots, whereas perceived enjoyment is found to exert no effect. The research further discussed implications and future directions of research.